Studies directed toward the synthesis of hedycoropyrans: total synthesis of des-hydroxy (-)-hedycoropyran B (ent-rhoiptelol B) - Kataria, Priyanka; Nomula, Rajesh; Kontham, Ravindar (Organic & Biomolecular Chemistry, 2022)
A full account of our efforts directed towards the synthesis of the diarylheptanoid-derived natural products hedycoropyrans that led to the total synthesis of ent-rhoiptelol B is described. In this endeavor, we have attempted two distinct synthetic strategies to access hedycoropyrans A and B, which led us to establish a facile synthetic route for des-hydroxy (-)-hedycoropyran B (ent-rhoiptelol B) from simple and readily accessible building blocks of 4-allylanisole and vanillin, employing Sharpless asymmetric epoxidation, CBS reduction, and an intramolecular AgOTf-catalyzed oxa-Michael reaction of suitably functionalized hydroxy-ynone as key transformations. The investigations disclosed herein will provide insights into designing novel synthetic routes for THP-DAH-derived natural products.